Synthesis of Artificial Zeolite from Coal Fly Ash by Alkali Treatments - Triyatmo, Bambang (Jurnal Zeolit Indonesia, 2004)
Coal fly ash was treated with alkali (NaOH) water solution by heating up to about 100 oC for 12 and 24 hours. The coal fly ash used in this experiment was obtained from PLTU (Steam Power Electric Station) Suralaya, West Java, Indonesia. It was passed through a wire sieve with filter size of 46 mm. The NaOH solutions were reacted 0.5, 1.0, 1.5, 2.5, 3.5 and 4.5 M. The final products of the reactions were designated as âartificial zeolitesâ. Result of this experiment indicated that the cation exchange capacity (CEC) of âartificial zeolitesâ were increased by increasing NaOH concentration up to 2,5 M. Higher CEC value of the 24 hours treated coal fly ash than that of the 12 hour treated ones. The CEC of âartificial zeolitesâ increased by about 50 time for the coal fly ash. The XRD (X-ray Diffraction) pattern of the coal fly ash treated by 2,5 M NaOH which had highest CEC value were present new crystalline matters (possibility phillipsite) with sharp diffraction peaks at 2.7, 3.2, 3.3, 4.1, 5.1, 7.1 Ã. The infrared (IR) spectrum of the âartificial zeoliteâ exhibited the broad absorption band around 1,000 cm-1 and at about 3,500 cm-1. The analyzed âartificial zeoliteâ showed steep descent around 100 oC in TG (Thermogravity), a small endothermic peak below 100 oC and a deep endothermic peak from 130 oC in DTA (Differential Thermal Analysis), representing presence of micropore structure of new zeolite species (probability phillipsite). The scanning electron micrograph of the âartificial zeoliteâ showed spherical structure with chinks formed in the 2,5 M NaOH treatment.